Isolation and characterization of nanocrystalline cellulose from oil palm biomass via transition metal salt catalyzed hydrolysis process / Chen You Wei - Chen, You Wei (2017)
Nanocellulose is an interesting and renewable material in the nanotechnology field. It can be prepared from natural cellulose via various chemical treatments. Because of its nano-scale dimensions, nanocellulose exhibits various outstanding and excellent physicochemical properties as compared with typical micro-sized dimension cellulose material, such as large surface area, high porosity, high aspect ratio, excellent tensile strength and modulus, and biodegradability. Conventionally, concentrated mineral acids (such as H2SO4, HCl, and HNO3) have been used to prepare nanocellulose via hydrolysis of cellulose derived from lignocellulosic biomass. However, such treatment is highly corrosive and probably destroys the overall hierarchical structure of the cellulose with very poor yield. In this research, the focus is priority given to overcome these drawbacks by using transition metal based catalysts, namely Fe(III), Co(II), Ni(II), Cr(III), Mn(II) as a highly potential hydrolyzing catalyst assisted with dilute sulfuric acid by converting cellulose fiber into nanoscale structure. Previous studies have been widely reported that transition metal salts act as Lewis acid catalyst, which is less corrosive and effective in hydrolyzing the bonding systems of the cellulose structure into smaller dimensions. This project is divided into three main sections: (i) Catalytic screening for hydrolysis of cellulose to nanocellulose; (ii) Optimization study of nanocellulose production by using response surface methodology (RSM); and (iii) Facile production of nanocellulose from oil palm empty fruit bunch (OPEFB) via one-pot oxidative-hydrolysis isolation approach. The results demonstrated that the Cr(III)- transition metal based catalyst rendered better hydrolysis efficiency, which the yielded nanocellulose possessed of the highest crystallinity index (75.6%) among the other catalysts. In order to optimize operating conditions, a central composite design (RSM-CCD) system was conducted by manipulating the independent hydrolysis variables, including reaction temperature (x1), reaction time (x2), Cr(NO3)3 concentration (x3) and H2SO4 concentration (x4). Responses were selected in terms of crystallinity index (y1) and product yield (y2) of nanocellulose. The hydrolysis efficiency of catalytic acid was greatly enhanced in the presence of catalyst, and the synergistic effect of H+ (from H2SO4) and Cr3+ cations could further increase the nanocellulose crystallinity as compared with hydrolysis system that catalyzed by either dilute acid or metal salt alone. Under the RSM optimized operational conditions at 82 °C, 0.22 M Cr(III)-transition metal based catalyst and 0.80 M H2SO4 with 1 h of reaction, the yielded nanocellulose was observed in the form of interconnected spider-web-like network structure with the average diameter of 18.4 ± 7.3 nm. TGA results suggested that the thermal stability of the optimized nanocellulose was mainly affected by the active sulfate groups, which is form H2SO4 solution and shorter chain of hydrolyzed cellulose. In summary, it can conclude that the proposed hydrolysis approach, which is Cr(III)-transition metal based catalyst assisted with dilute sulfuric acid is highly efficient for hydrolysis of cellulose to nanocellulose with high yield of 82.9%. In addition, the one-pot oxidative-depolymerization process had been developed in order to isolate nanocellulose from oil palm empty fruit bunch. Results revealed that the one-pot isolated nanocellulose rendered higher crystallinity (80.3%) and better thermal stability (320 °C) as compared with conventional multistep purification process (75.4% and 307 °C). Besides that, the nanocellulose prepared via one-pot isolation had higher yield of 42% compared to the multistep process (∼27.5%). In summary, Cr(III)-transition metal based catalyst is able to produce higher crystallinity nanocellulose with greater yield due to its high selectively towards cellulose hydrolysis under mild reaction conditions. Also, the trivalent state chromium transition metal based catalyst was capable of reacting with more electrons in glucose units and eventually resulted in the cleavage of bonding system.